先化简 再求值.(2a-b)^3(b+2a)^4÷【-3分之一(2a+b)(2a-b)】^3
1个回答
(2a-b)^3(b+2a)^4/[(2a+b)(2a-b)/(-3)]^3
=(2a-b)^3(b+2a)^4*(-3)^3/(2a+b)^3(2a-b)^3
=-27(2a+b)
相关问题
先化简,再求值:[(3a+2b)(3a-2b)-(a+2b)(5a-2b)]÷4a,其中a=2,b=-3
先化简再求值,[(2b-a)(3a+2b)-(a+2b)²]÷(-0.5a)
先化简再求值(3a-2b)(3a+2b)+2ab³÷(-ab),其中a=-2,b=-1.
先化简,再求值:(√a+√b)²-(√a-√b)²,其中a=2+√3,b=2-√3
先化简,再求值:(2a+b)(2a-b)+3(2a-b)2+3a(4a-3b),其中a=-1,b=2.
先化简再求值(2a+b)(2a-b)+3(2a-b)^2+(-3a)(4a-3b)其中a=-1,b=-2
(3a+4b)^2-(3a-b)(2a+b )-2(a-2b)(2b+a)先化简再求值其中a等于二分之一,b等于1
先化简,再求值:(a+b)(a-b)+(4ab^3-8a^2b^2)÷4ab,其中a=2.b=1
先化简,再求值:(a-b)(a-2b)-(3a-2b)(a-3b),其中a=4,b=-1
先化简,再求值:2(3a²b-ab²)-4a²b+5-3(3分之2a²b-ab&